Relaksasi Autogenik untuk Meningkatkan Regulasi Emosi pada Siswa SMP - Yulia Fitriani; Asmadi Alsa (Faculty of Psychology, Universitas Gadjah Mada, 2015)
This study aims to empirically examine the effect of autogenic relaxation training to increase the emotion regulation of the junior high school students. The Subjects in this study were the students of Junior High School M Yogyakarta. The selection of research subjects was based on the lowest pretest scores students got from the scale of emotion regulation, and the number of the sebject taken was 50 students. The placement of subjects into control and experimental group performed by using random assignment. The number of the subjects who followed the pretest, the posttest and the follow-up in full in the experimental group was 16 female students. While in the control group, the number was 19 female students. The results showed that the re was a significant difference between the pretest and the posttest scores in both groups experimental control). The conclusion of this study is autogenic relaxation was effective to improve the emotion regulation of the junior high school students.